As mulheres da capa: uma análise semiótica de traços, cores e performances ilustrados na revista feminina Grande Hotel em finais da década de 40 - Aquino, Denise Marciano de (2012)
The "body" transcends its material condition of existence, marks, designs and shows a being staying in a world shaped by realities which make it tactile, albeit subjective, vibrating, and at the same time encased in standards. Volatile, even if you want it to be everlasting. These realities are embroidered by ideals of beauty, which converge into aesthetic standards that are persistently. Which are the Processes that reflect the representation of a "body" that is considered ideal? The initial hypothesis is that the media aimed at female audiences defile / is contaminated by aesthetic standards of beauty woven into a kaleidoscope in which cultural practices embroider a mosaic bio-political and socio-cultural.It is worth remembering that when I consider the female audience, I assume that the "beauty" is often related to it. In this study, therefore, I believe that women's magazines are an important source to investigate the question posed: by means of linguistic and visual resources this media establishes a will and a duty to be "beautiful." The female reader has access to a kind of knowledge and power that can be incorporated to make her "beautiful", sanctioned by the society and the public for whom it is aimed. The magazine that introduced the photo-story in Brazil will be analyzed in this study: it is the Grand Hotel, whose weekly editions circulated between 1947 and 1980.Covers published in its first year of service are being analyzed; a kind of "artistic work", they are drawn by hand and function as an identification of the journal. The choice of this analysis material is due to the cultural ideology of the late 40'sThe analysis is grounded in a proposal which, in addition to a system of signs, the culture is understood as a light of traditional theories of communication and arts magazines and translated into a new dimension of knowledge - which considers the need for a change of fields and methods of application .This research focuses on how a media production is related to cultural series, redesigning and distributing porous and non-orthogonal forms of beliefs, values and ways of life, exchanging cross bordering translations whose threads I intend to investigate. This work is based therefore on theoretical aspects of communication and the arts (especially in the semiotic work of the Slavic extraction, among which, Tynianov, Lotman and others). Three chapters compose the dissertation: the first chapter checks cases in which the contamination between codes, sets and languages inscribed in bodies (considered ideal) embroidered in a double subjectivity in which the natural and cultural are intertwined. Chapter 2 covers "printed aesthetic universes" it deals with the emergence of the magazine, relating this media with an aesthetic language of the universe. The proposed analysis of the corpus are developed in Chapter 3. Some final remarks close the paper, and opportunities for future research in the area are also highlighted